2014
DOI: 10.1073/pnas.1403353111
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of disease and carriage isolates of nontypeable Haemophilus influenzae identifies discrete population structure

Abstract: Significance Several human pathogens exploit genomic variability to adapt to the host environment. Genome sequencing of collections of isolates and classification of strains according to their genomic content are pivotal to the formulation of vaccines able to elicit broad protection. We sequenced a collection of carriage and disease isolates of nontypeable Haemophilus influenzae , a component of the microbial flora of the upper respiratory tract that can cause a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
137
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(156 citation statements)
references
References 63 publications
19
137
0
Order By: Relevance
“…This hunt for microbial genes or mutations associated with disease continues to this day. For example, researchers are applying genomics to try to discern signatures of virulence among S. aureus, Haemophilus influenzae and Enterococcus faecium strains, to name a few [2][3][4] .…”
Section: Context Is Everythingmentioning
confidence: 99%
“…This hunt for microbial genes or mutations associated with disease continues to this day. For example, researchers are applying genomics to try to discern signatures of virulence among S. aureus, Haemophilus influenzae and Enterococcus faecium strains, to name a few [2][3][4] .…”
Section: Context Is Everythingmentioning
confidence: 99%
“…This genomic dissimilarity between fucP-negative and conventional fucP-positive strains previously led us to also propose that fucP-negative strains, while closely related to H. influenzae, might comprise a novel 'fuzzy' Haemophilus species [6]. However, this distance RESEaRch aRticlE Price [18], at the time the largest comparative genomic analysis of H. influenzae. We have since shown that Clade I H. influenzae and fucP-negative strains share a node [6], implying that they have shared ancestry.…”
Section: • Phylogenomic Analysis Of Haemophilus Spp For Species Detementioning
confidence: 94%
“…genomes were available for this study: 316 H. influenzae (145 generated in the current study, 19 unpublished and 152 published elsewhere [6,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]), 59 H. haemolyticus (44 generated in the current study, one unpublished and 14 published elsewhere [6,26,28,[35][36] Table 1). The hypD assay differentiates H. haemolyticus (red) from all other species and the siaT assay differentiates H. influenzae (blue), 'Clade I' H. influenzae (purple) and fucose operon-negative H. influenzae strains (green) from all other species.…”
Section: • Haemophilus Genomesmentioning
confidence: 99%
See 2 more Smart Citations